Physical Therapy Management for Post OP Tibia Plateu Dextra: A Case Study - Prasetyo, Hanif Kemal; Widodo, Agus; Putra, Guntur Rusmana (Universitas Muhammadiyah Surakarta, 2022)
Introduction: Fracture or fracture is a form of bone continuity disorder caused by direct or indirect trauma. Fracture treatment is divided into 3 stages, namely restoring the position of the bone to its anatomical shape, maintaining the position of the bone for some time / immobilization and restoring function / rehabilitation, so that a patient will be able to return to activities without significant obstacles. Physiotherapy with various exercise therapy modalities can reduce pain and improve LGS so that patients can be active and productive again. Exercise therapy that is usually given to improve LGS is conventional exercise therapy such as passive stretching and special mode exercise therapy such as hold relax.Case Presentation:Mrs. T was 52 years old on May 6, 2022 while walking the patient fell while descending 1 stair due to wrong support and then fell with support on the outer right knee which caused the bone to fracture / crack after that surgery was carried out on May 7 , 2022 and the patient was treated for 4 days until May 11, 2022. After that the patient is referred by a rehabilitation doctor to perform physiotherapy actions at PKU Muhammadiyah Sukoharjo Hospital Management andOutcomes:Patients undergo therapy three times in two weeks with a physiotherapy program that includes Infra Red, TENS, Quadriceps Set, Hamstring and Gastroc Stretching, Mobilization Exercises on the legs, Kicking exercises using Ankle, Kicking exercises with the therapist's body resistance. Patients were evaluated using the Visual Analog Scale (VAS) and Manual Muscle Testing (MMT).Conclusion:After receiving physiotherapy treatment with physiotherapy modalities and exercise therapy plus a home program that has been carried out by the patient, the results are decreased pain, increased muscle quality and decreased edema in the patient's right leg.